Spatio-temporal variation and coupling coordination relationship between urbanisation and habitat quality in the Grand Canal, China. (June 2022) - Tang, Feng; Wang, Li; Guo, Yiqiang; Fu, Meichen; Huang, Ni; Duan, Wensheng; Luo, Ming; Zhang, Jianjun; Li, Wang; Song, Wei
Abstract: Urbanisation leads to dramatic changes in regional land use, which significantly affects habitat quality. Research on the coupling coordination relationship between urbanisation and habitat quality is conducive to promoting regional ecological environment improvement and urban sustainable development. In this article, we adopted the InVEST model and linear weighted sum method separately to evaluate the spatio-temporal variation characteristics of habitat quality and urbanisation level of the Grand Canal. Then, we used the coupling coordination degree model (CCDM) to investigate the interactive coercing relationship between urbanisation and habitat quality. The purpose was to provide reference for future implementation of ecological conservation work along the Grand Canal and formulation of sustainable urban development strategies. The results showed that habitat quality has continued to decline from 1990 to 2018. After becoming a world cultural heritage site, the habitat quality of the partial reaches has improved. The comprehensive urbanisation level and the four subsystem urbanisation levels, including demographic urbanisation, spatial urbanisation, economic urbanisation, and social urbanisation, of 35 cities along the Grand Canal have all steadily increased from 1990 to 2018. The social urbanisation level was obviously lower than the urbanisation levels of the other three dimensions in most cities along the Grand Canal, indicating that the quality of urbanisation seriously lags behind the speed. The coupling coordination degree (CCD) between the urbanisation level of each city and the habitat quality of the reaches in the corresponding city exhibited a fluctuating but increasing relationship. Most cities have developed in a more coordinated direction and very few cities have deteriorated. Meanwhile, the coupling coordination characteristics between urbanisation level and habitat quality have constantly changed, from the urbanisation lagged type to the urbanisation-habitat synchronised type and the habitat quality lagged type. This article has important value for implementing the ecological conservation and restoration projects of the Grand Canal, optimizing land management policies, and improving the sustainable development level of cities along the Grand Canal. Highlights: New perspective for the study of the relationship between ecological environment and socio-economic activities. Becoming a world cultural heritage helps to improve the habitat quality of the Grand Canal. Successful application for world cultural heritage did not hinder urbanisation development. Urbanisation quality of most cities seriously lagged behind the urbanisation speed. The relationship between habitat quality and urbanisation have developed in a more coordinated direction.